Advances in the treatment of invasive neonatal candidiasis - Botero-Calderon, Lorena (Expert Opin Pharmacother, 2015)
INTRODUCTION: Invasive candidiasis is responsible for approximately 10% of nosocomial sepsis in very-low-birth-weight (VLBW) infants and is associated with substantial morbidity and mortality. Over the last 2 decades, the antifungal armamentarium against Candida spp. has increased; however, efficacy and safety studies in this population are lacking. AREAS COVERED: We reviewed the medical literature and extracted information on clinical and observational studies evaluating the use of antifungal agents in neonates with invasive candidiasis. EXPERT OPINION: Efficacy and safety data for antifungals in neonates are lacking, and the majority of studies conducted to date have concentrated on pharmacokinetic/pharmacodynamic evaluations. Unlike other anti-infective agents, efficacy data in the setting of neonatal candidiasis cannot be extrapolated from adult studies due to differences in the pathophysiology of the disease in this population relative to older children and adults. Data collected thus far or data submitted to regulatory agencies for amphotericin B deoxycholate, fluconazole, and micafungin suggest that these are the current agents of choice for this disease in neonates until data for newer antifungal agents become available. For prophylaxis, data from fluconazole randomized controlled trials will be submitted to the regulatory agencies for labeling. Ultimately, the field of therapeutics for neonatal candidiasis will require multidisciplinary collaboration given the numerous challenges associated with conducting clinical trials in neonates.